The Cartoon quality in Internet. Clan TVE, Neox Kidz and Boing: entertainment platforms for young audiences - Inmaculada Sánchez-Labella Martín (Index Comunicación, 2016)
With the advancement of technology, Internet it has become the primary means for audiovisual consumption while presenting a critical situation around the debate the quality of the content. With the emergence of DTT (Digital Terrestrial Television) in Spain television networks, public and private, they have created new thematics channels focused on content for children. At the same time, with the rise of new electronic devices such as tablets and smartphones, they have moved such content to the network by creating of platforms whose programs are aimed childhood. The non-linearity and immediacy in consumption make the Internet becomes an active mean giving autonomy and freedom to access a multitude of content regardless of time and the device. In this situation the child consumers is the audience that worries both parents and educational institutions. Restless, therefore, that children do not find programs adjusted to their age. The quality concept harbors no concrete definition because of the multitude of factors and perspectives that influence it. This paper, and based on different measurement criteria set by countries like Argentina, Chile, Spain, France, Italy, Japan, Sweden, the University of Pennsylvania (USA) or the ACTF (Australian Children´s Television Foundation) poses as main objective to analyze the online platforms Clan RTVE, Neox Kidz and Boing of television TVE, Antena 3 and Telecinco, respectively, because they are considered spaces with audiovisual material created for children. With the intention of demonstrating that they are presented as quality environments for children who access them it will conduct a qualitative methodology. Using the content analysis technique to each of the animated titles we can say that the cartoons, as outlined above, are quality entertainment programs.